Peran Pengurus Panti Asuhan dalam Menunjang Keberlanjutan Pendidikan Anak di Panti Asuhan Muhammadiyah Cingkariang - Haulia Tris Finanda; Hidayani Syam (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
The aims of this research is to investigate the role of caretakers insupporting the continuance of the children's education, the obstacles face by the caretakers in carrying out the role, and caretakers attempt in overcoming the obstacles. In this study the method used is the 2 descriptive. With the techniques of data collection used are direct observation techniques, direct communication techniques and documentary studies techniques, while the tools of data collection are observation, interview and documentation. The analysis conducted using qualitative descriptive with 7 participants consist of 2 orphanage caretakers, 2junior high student’s orphans, 2 senior high student’s orphans and 1 university student orphan. The roles of the orphanage caretakers in supporting the continuance of the children’s education is as the motivator, facilitator, mentor, and a foster parent as a replacement of the families or parents of the children. The obstacles faced by the caretakers in carrying out its’ role is derived from the children’s own self and funding. The efforts of the caretaker used to resolve existing obstacles is by approaching the child, finding donors to help the orphanage funding and facilitate all the needs of the children in the orphanage.